2018
DOI: 10.1074/jbc.ra118.003410
|View full text |Cite
|
Sign up to set email alerts
|

Long-range function of secreted small nucleolar RNAs that direct 2′-O-methylation

Abstract: Small nucleolar RNAs (snoRNAs) are noncoding RNAs that guide chemical modifications of structural RNAs. Whereas snoRNAs primarily localize in the nucleolus, where their canonical function is to target nascent ribosomal RNAs for 2'--methylation, recent studies provide evidence that snoRNAs traffic out of the nucleus. Furthermore, RNA-Seq data indicate that extracellular vesicles released from cells contain snoRNAs. However, it is not known whether snoRNA secretion is regulated or whether secreted snoRNAs are fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 48 publications
(60 reference statements)
0
51
0
Order By: Relevance
“…Efforts to characterize tissue-specific noncoding transcripts have recently resumed with the advent of RNA sequencing (RNA-seq), which greatly advanced the discovery of novel and previously undetected miRNA (24,25). However, no prior study encompasses a spectrum of mammalian tissues from both female and male individuals, nor includes the other noncoding RNA types that have recently been identified to carry out tissue-and cell type-specific functions (26,27).…”
mentioning
confidence: 99%
“…Efforts to characterize tissue-specific noncoding transcripts have recently resumed with the advent of RNA sequencing (RNA-seq), which greatly advanced the discovery of novel and previously undetected miRNA (24,25). However, no prior study encompasses a spectrum of mammalian tissues from both female and male individuals, nor includes the other noncoding RNA types that have recently been identified to carry out tissue-and cell type-specific functions (26,27).…”
mentioning
confidence: 99%
“…[1,10] These are the representative pathologies of HD, thus extending the survival of HD mice. The positive effect ofheterochronic parabiosis originates from the shared blood circulation, [25,26] just like the other neurodegenerative diseases ameliorated by heterochronic parabiosis. [9,27,28]It is worth noting that the R6/2 mice die typically at around 3-4 months of ageaccompanied by trimming and muscle loss [10,11] and highly vulnerable to stress.…”
Section: Discussionmentioning
confidence: 99%
“…We also showed that electroporation can introduce mRNAs into EVs for a later functional translation in the recipient cells [ 49 ]. Non-coding RNA found in EVs include small non-coding RNA, such as small nucleolar RNAs [ 129 ], microRNAs [ 130 ], and piwi-interacting RNAs [ 131 ], and other long non-coding RNAs [ 132 ]. The most studied among them are microRNAs, given the well-known regulatory role of microRNAs and their abundance in EVs [ 133 ].…”
Section: Biochemical Properties Of Evs and Their Intrinsic Advantamentioning
confidence: 99%